Implementasi Karakter Kejujuran Melalui Pembelajaran PKn di SMP Kota Bengkulu - Zulyan, Zulyan; At, Atri Oktari; Qurniati, Amnah; Hasibuan, Muslih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the implementation of the character of honesty through civic education learning at SMPN 17 Bengkulu City and the inhibiting factors in implementing the character of honesty through learning civics education. This research is a type of qualitative research. The research subjects are civic education teachers and students. The results of this study indicate that the implementation of the character of honesty through civic education learning at SMP Negeri 17 Bengkulu City is realized in the learning process, namely by habituation. Factors that hinder the implementation of the character of honesty through civic education learning include time, student environment, different backgrounds, different student characters, and lack of a culture of shame. In conclusion, the honest character of students in this school shows good character. However, there are some honest characters, such as not lying and not cheating, which are still done by students, there are still students who cheat when doing exercises and homework (PR). In the application of honest characters such as not lying and being trustworthy, the teacher makes habituation, then sets an example so that students can be trusted, and assignments so that students do not cheat. Keywords: Implementation of honest character, Pkn Learning